AQUA Mutant Protein Quantification of Endomyocardial Biopsy-Sized Samples From a Patient With Hypertrophic Cardiomyopathy - Becker, Edgar; Francino, Antonio; Pich, Andreas; Perrot, Andreas; Kraft, Theresia; Radocaj, Ante (Frontiers in Cardiovascular Medicine, 2022)
In genetic diseases like hypertrophic cardiomyopathy, reliable quantification of the expression level of mutant protein can play an important role in disease research, diagnosis, treatment and prognosis. For heterozygous β-myosin heavy chain (β-MyHC) mutations it has been shown that disease severity is related to the fraction of mutant protein in the myocardium. Yet, heart tissue from patients with genetically characterized diseases is scarce. Here we asked, if even in the case of small endomyocardial biopsies, single quantifications produce reliable results. Myocardial samples were taken from four different regions of an explanted heart of a patient with hypertrophic cardiomyopathy carrying point mutation p.Gly716Arg in β-MyHC. From both, large samples (15 mg) and small, endomyocardial biopsy-sized samples (≤ 1 mg) myosin was extracted and enzymatically digested to yield a specific peptide of interest that allowed to distinguish mutant and wild-type β-MyHC. Absolute quantification by mass spectrometry (AQUA) of the peptide of interest was performed repeatedly for both sample sizes to determine the fraction of mutant β-MyHC Fractions of mutant β-MyHC (32% on average) showed only small differences between the four cardiac regions and for large and small samples. The standard deviations were smaller than 5 percentage points for all cardiac regions. The two quantification methods (large and small sample size) produce results with comparable accuracy and precision. Consequently, with our method even small endomyocardial biopsies allow reliable protein quantification for potential diagnostic purposes.